1981
DOI: 10.7326/0003-4819-94-5-611
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Pulmonary Cryptococcosis

Abstract: Over 14 years 41 patients were diagnosed as having pulmonary cryptococcosis. Cryptococcus neoformans remained localized to the lung in 12 cases and disseminated in the remaining 29. Thirty-four patients were compromised hosts. Disseminated disease developed in 28 of these 34, and four of these 28 patients with disseminated disease presented with concomitant pulmonary and meningeal infections. In all the remaining 24 central nervous system involvement developed 2 to 20 weeks after the finding of an abnormal che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(30 citation statements)
references
References 7 publications
1
29
0
Order By: Relevance
“…M. catarrhalis has recently emerged as a true pathogen and is now considered to be an important cause of upper respiratory tract infections in healthy children and elderly people, while it causes severe infections in immunocompromised hosts. S. aureus can cause diseases such as otitis media, and is also known to cause secondary infection in influenza patients-subsequently causing death (Kerkering et al, 1981;Aberg et al, 1999;Nester et al, 2001;Verduin et al, 2002). Many of the rural inhabitants are subjected to a poor socio-economic environment with crowded living conditions where a number of communicable diseases become prevalent.…”
Section: Antimicrobial Screeningmentioning
confidence: 98%
“…M. catarrhalis has recently emerged as a true pathogen and is now considered to be an important cause of upper respiratory tract infections in healthy children and elderly people, while it causes severe infections in immunocompromised hosts. S. aureus can cause diseases such as otitis media, and is also known to cause secondary infection in influenza patients-subsequently causing death (Kerkering et al, 1981;Aberg et al, 1999;Nester et al, 2001;Verduin et al, 2002). Many of the rural inhabitants are subjected to a poor socio-economic environment with crowded living conditions where a number of communicable diseases become prevalent.…”
Section: Antimicrobial Screeningmentioning
confidence: 98%
“…These patients showed an excel lent response to fluconazole. Kerkeringet al [17] reported cryptococcal lesions in the skin that antedated central ner vous system disease by weeks to months in 20% of their patients.…”
Section: Discussionmentioning
confidence: 99%
“…If diagnosis of pulmonary cryptococcosis had been achieved, and antifungal therapy given, then cryptococcal meningitis could have been prevented and his vision could have been saved. In a study done by Kerkering et al, 14 CNS cryptococcosis developed two to 20 weeks after an abnormal chest roentgenogram. The conclusion of that study was that the natural history of untreated pulmonary cryptococcosis in a compromised host is extrapulmonic dissemination and these patients should receive antifungal therapy to prevent such an event.…”
Section: Discussionmentioning
confidence: 99%